CIVIC PARTICIPATION OF THE UKRAININ YOUTH DURING THE WAR - Bidenko, Yuliya (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
This article examines the transformation of civic participation among Ukrainian youth during the full-scale war, focusing on patterns of engagement, institutional adaptation, and structural constraints. Ukrainian civil society has historically evolved in waves, intensifying during periods of political upheaval and external threats; however, since 2014, and especially after 2022 when the youth participation has undergone both quantitative and qualitative expansion. Empirical evidence demonstrates a sharp rise in volunteer engagement. The study argues that in the Ukrainian context, the distinguishing between volunteering and civic activism is increasingly blurred due to the broad legal definitions, and hybrid practices that combine service provision with advocacy, cultural, artistic, educational activities, and political engagement.Key areas of youth participation include humanitarian aid, support for war-affected populations, reconstruction efforts, grassroots initiatives, cultural activities, and informal education. Mostly young people get involved throughout their social group i.e. friends, relatives, colleagues or schools’ and universities self-government. The role of youth civil society organizations, informal initiatives, and digital platforms as mobilization tools is also highlighted. At the same time, a lot of young people remain outside formal civil society institutions, reflecting persistent socio-economic, regional, and educational barriers. The article also addresses the impact of war-related trauma, loss, displacement, and inequality on participation, particularly among vulnerable groups, and youth from the regions affected by the Russian Ukrainian war mostly. Despite a high willingness to contribute to community recovery in the future, many young people report low perceived political efficacy and limited understanding of participation mechanisms, as well as the lack of a success stories, good examples, and weak feedback from the local and governmental authorities. The findings point to the emergence of a flexible yet structurally fragile model of civic engagement that requires sustained institutional support and inclusive policy interventions in the post-war period.